Повышение степени вытяжки тонколистовых деталей при пневмоударной штамповке жидкостью - Фролов, Е. А.; Кравченко, С. И.; Носенко, О. Г.; Ясько, С. Г. (НТУ "ХПИ", 2014)
Рассмотрены, а также аналитически и экспериментально исследованы пути повышения степени вытяжки тонколистовых деталей методом пневмоударной штамповки жидкостью. Получены зависимости, позволяющие проектировать технологический процесс высокоскоростной штамповки тонкостенных деталей за счет искусственного регулирования величин протяжных ребер формообразующих матриц на пневмоударном оборудовании модели Т1324 штамповки жидкостью

Ways to increase drawing degree of sheet parts in liquid pneumatic-mechanical forming are considered as well as analytically and experimentally researched. The dependencies that allow manufacturing process design of high-speed stamping of sheet-metal parts controlled by the size of artificial drawing ribs of forming dies for Т1324 liquid pneumatic-mechanical forming machinery were obtained
Increasing drawing degree of sheet parts in liquid pneumatic-mechanical forming
Keywords: тонколистовое формообразование; технологический процесс; высокоскоростная вытяжка; деформирование; high-speed drawing; drawing degree; liquid pneumatic-mechanical forming; sheet parts; manufacturing process